METODE RESITASI DAN DISCOVERY LEARNING PADA KEMAMPUAN PEMAHAMAN GEOMETRIS SISWA KELAS VII - Marchasan Lexbin Elvi Judah Rijanto; Tyara Kamandawi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Every learning that takes place must lead each student to the optimal competency achievement at least as required by the applicable curriculum. And in line with the implementation of the 2013 national education curriculum, the expectation of student competency achievement in mathematics learning rests, among others, on the discovery learning method treatment. This is an encouragement for researchers to examine whether direct learning in this case the recitation method can give the same hope and find the truth by looking at the comparison of the achievement of student competencies in learning geometry material for class VII students as well as seeing differences in student attitudes towards learning and mathematics and continued by looking the relationship between the two. The instrument used was in the form of 4 essay items that measured the students 'geometric understanding skills, both mechanical and relational, and non-test instruments that saw students' self-confidence, anxiety and motivation to succeed in mathematics. Subjects were students from two seventh grade students of SMP ARROYAN Bogor, which is a medium-level education unit for the 2019/2020 school year with no different mathematical abilities. And based on the results of statistical tests obtained results; The achievement of geometric comprehension abilities of seventh grade students who are subjected to the discovery learning method and those who are subjected to the recitation method is no different. Also the attitudes of students are not different and the relationship between the two is not real. So that the recitation method is good to be used as an alternative treatment in geometric learning for seventh grade students from the medium middle level education unit.